Evidence for activation of endogenous transporters in Xenopus laevis oocytes expressing the Plasmodium falciparum chloroquine resistance transporter, PfCRT. - Nessler, Susanne; Friedrich, Oliver; Bakouh, Naziha; Fink, Rainer; Sanchez, Cecilia P; Planelles, Gabrielle; Lanzer, Michael (Journal of Biological Chemistry, 2004)
A large body of genetic, reverse genetic, and epidemiological data has linked chloroquine-resistant malaria to polymorphisms within a gene termed pfcrt in the human malarial parasite Plasmodium falciparum. To investigate the biological function of the chloroquine resistance transporter, PfCRT, as well as its role in chloroquine resistance, we functionally expressed this protein in Xenopus laevis oocytes. Our data show that PfCRT-expressing oocytes exhibit a depolarized resting membrane potential and a higher intracellular pH compared with control oocytes. Pharmacological and electrophysiological studies link the higher intracellular pH to an enhanced amiloride-sensitive H(+) extrusion and the low membrane potential to an activated nonselective cation conductance. The finding that both properties are independent of each other, together with the fact that they are endogenously present in X. laevis oocytes, supports a model in which PfCRT activates transport systems. Our data suggest that PfCRT plays a role as a direct or indirect activator or modulator of other transporters.